Fractal Dynamics of Stride Interval Fluctuations: Children With Spastic Diplegia - Rizvi, Sidra; Chau, Tom; Kwan, Hon (CMBES Proceedings, 2002)
The temporal fractal dynamics of gait in children with spastic diplegia were quantified, and the relationship between these fractal dynamics and mobility levels as measured by the Gross Motor Function Measure (GMFM) were investigated. A volunteer sample of 13 children with a mean age of 6.1 ± 0.97 years, with Spastic Diplegia participated in the study. Fluctuations in stride interval times were examined at different window sizes (scales), which characterized the fractal (statistical self-similarity) properties of the time series by a scaling exponent. Participants with Spastic Diplegia were found to have a mean scaling exponent value of 0.69 ± 0.12, deviating significantly (p<0.05) from published values for age-matched able-bodied children (0.92 ± 0.07). GMFM scores were poorly related to scaling exponent values. Fluctuations in the stride interval are believed to be governed by supraspinal neurological mechanisms. Deviations from scaling exponent values of able-bodied children suggest neurological pathology, the exact nature of which remains unknown.